1996
DOI: 10.2307/2527445
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty, Investment, and Industry Evolution

Abstract: We study the effects of aggregate and idiosyncratic uncertainty on the entry of firms, total investment, and prices in a competitive industry with irreversible investment. We first use standard dynamic programming methods to determine firms' entry decisions, and we describe the resulting industry equilibrium and its characteristics, emphasizing the effects of different sources of uncertainty. We then show how the conditional distribution of prices can be used as an alternative means of determining and understa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
161
0
3

Year Published

1999
1999
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 263 publications
(166 citation statements)
references
References 9 publications
2
161
0
3
Order By: Relevance
“…Following some previous studies, we expect that unforeseeable demand negatively a¤ects the incentives of …rms to innovate. Especially, it might discourage persistent innovation (see Caballero and Pindyck, 1996;Czarnitzki and Toole, 2008). The asymmetries between …rms are captured by the parameter in the theoretical model.…”
Section: Data and Variablesmentioning
confidence: 99%
“…Following some previous studies, we expect that unforeseeable demand negatively a¤ects the incentives of …rms to innovate. Especially, it might discourage persistent innovation (see Caballero and Pindyck, 1996;Czarnitzki and Toole, 2008). The asymmetries between …rms are captured by the parameter in the theoretical model.…”
Section: Data and Variablesmentioning
confidence: 99%
“…Caballero's (1991) analysis of the effect of uncertainty on investment concludes that "If this effect is sufficiently strong (i.e., the asymmetry of adjustment costs is large and the negative dependence of the marginal profitability of capital on the level of capital is strong), the investment-uncertainty relationship becomes negative. The irreversibleinvestment arguments analyzed in the literature typically correspond to this case."…”
Section: Introductionmentioning
confidence: 99%
“…As the level of disaggregation of the data increases, the larger will be the impact of idiosyncratic shocks compared to economy-wide or industry-wide ones, at least for competitive industries. 37 Instead, when studying investment at a more aggregated level, as in this case at industry level, the uncertainty that matters would be the industry-wide one, because the 37 See Caballero and Pindyck (1996) who compare the volatility of marginal profitability of capital for 2-digit industries and the mean of volatility for the 4-digit industries that make up each 2-digit sector, showing that the latter is always higher by a factor of two or three. They explain this with the fact that total uncertainty is made up of idiosyncratic shocks and aggregate uncertainty, and the idiosyncratic shocks are predominant at the more disaggregated level.…”
Section: -Measuring Price Uncertaintymentioning
confidence: 99%
“…Bernanke (1983) had argued that aggregate and firm-specific shocks could conflict and cancel, altering the impact of uncertainty on investment behaviour. Bertola and Caballero (1994) found empirical evidence of this claim, while Caballero and Pindyck (1996) showed that the effects of uncertainty were usually stronger (if not clearer) at the disaggregated level. The survey by Carruth et al (2000) compare the available empirical evidence, and shows that the aggregate studies of the investmentuncertainty relationship usually find a significant negative sign, while the overall empirical results obtained from the applied works based on disaggregated data are less conclusive.…”
mentioning
confidence: 98%
See 1 more Smart Citation